Alcohol use among older adults: A comparative study across four European countries. Issue 6 (December 2020) - Rossow, Ingeborg; Træen, Bente
Aims: (i) To examine whether mean consumption and prevalence of at-risk drinking are highly correlated across samples of older adults, and (ii) to explore whether sociodemographic and health characteristics of alcohol use differ across countries. Method: Cross-sectional surveys were conducted in four European countries, Norway, Denmark, Belgium, and Portugal, applying identical data collection methods and survey instruments in general population samples of older adults aged 60 to 75 years. Alcohol consumption was measured as units of alcohol per week, which provided the basis for categorising the two outcome measures: abstention (0 units/week) and at-risk drinking (8+ units/week). Cross-tabulations and logistic regression models were estimated to examine associations between sociodemographic and health characteristics on the one hand and alcohol abstention and at-risk drinking on the other. Results: Prevalence of abstention was highest in Portugal and lowest in Denmark, whereas at-risk drinking was more prevalent in Denmark and Belgium compared to Norway and Portugal. Among country- and gender-specific samples of drinkers, there was a strong positive correlation between mean consumption and prevalence of at-risk drinkers. Female gender characterised abstention, whereas male gender characterised at-risk drinking in all four countries. Other sociodemographic characteristics and indicators of health and wellbeing were differently associated with abstention and at-risk drinking across the four countries. Conclusions: A strong regularity in the distribution of alcohol consumption was observed in the samples of older adults. Gender was the only common factor associated with drinking behaviour across the four countries.